ENGLISH ACADEMIC WRITING FOR THE STUDENTS OF TECHNICAL INFORMATION OF WIDYA DHARMA UNIVERSITY OF KLATEN - Ike Anisa & Sukasih Ratna Widayanti (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Writing is one of the main skill in learning English which is conclude on productive skill in the abilityof producing language. In the university, writing skill has an expected that the students couldmastering in the academic writing level. It has an aim that the students could write at least the abstractof their research paper in English. In Widya Dharma University of Klaten, the writing skill givenfrom the early semester integrated with the other three skills (listening, reading, and speaking). In theprocess of teaching and learning, it is found that the writing skill of the technical information studentswas not satisfying. This research is described the problems faced by the students in masteringacademic English writing in Technical Information of Widya Dharma University of Klaten. In thisresearch, the problems faced by the students is on the English vocabulary and the grammatical used inthe sentences.Keywords : Academic writing; vocabulary; grammatical